Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, (6/11+5/11)x3/17
c1:=1x3/17
=3/17
c2:=6/11x3/17+5/11x3/17
=18/197+15/187
=33/187
=3/17
b,3/5x7/9-3/5x2/9
c1:=21/45-6/45
=15/45
=1/3
c2:=3/5x(7/9-2/9)
=3/5x5/9
=1/3
c,( 6/7-4/7):2/5
c1:=2/7:2/5
=2/7x5/2
=5/7
c2,6/7:2/5-4/7:2/5
=6/7x5/2-4/7x5/2
=15/7-10/7
=5/7
d,8/15:2/11+7/15:2/11
c1:=(8/15+7/15):2/11
=1x11/2
=11/2
c2:=8/15x11/2+7/15x11/2
=88/30+77/30
=165/30
=11/2
a) (\(\frac{6}{11}\) + \(\frac{5}{11}\)) x \(\frac{3}{17}\)= \(\frac{11}{11}\) x \(\frac{3}{17}\)= \(1\) x\(\frac{3}{17}\)= \(\frac{3}{17}\)
b) \(\frac{3}{5}\)x\(\frac{7}{9}\)- \(\frac{3}{5}\)x \(\frac{2}{9}\) = \(\frac{3}{5}\)x (\(\frac{7}{9}\)- \(\frac{2}{9}\))= \(\frac{3}{5}\) x \(\frac{5}{9}\)= \(\frac{3}{9}\)
c) (\(\frac{6}{7}\)- \(\frac{4}{7}\)) : \(\frac{2}{5}\)= \(\frac{2}{7}\) x \(\frac{5}{2}\)= \(\frac{5}{7}\)
d) \(\frac{8}{15}\) : \(\frac{2}{11}\) + \(\frac{7}{15}\): \(\frac{2}{11}\)= ( \(\frac{8}{15}\)+ \(\frac{7}{15}\)) x \(\frac{11}{2}\)= 1 x \(\frac{11}{2}\)= \(\frac{11}{2}\)
Chúc học tốt nha!
A =\(\frac{2}{5}\times\frac{4}{7}+\frac{3}{5}\times\frac{4}{7}\) B = \(\frac{17}{13}\times\frac{12}{17}-\frac{4}{13}\times\frac{12}{17}\) C = \(\frac{9}{14}:\frac{6}{7}+\frac{5}{14}:\frac{6}{7}\) D =\(\frac{9}{12}:\frac{7}{9}\times\frac{12}{19}\)
= \(\frac{4}{7}\times\left(\frac{2}{5}+\frac{3}{5}\right)\) =\(\left(\frac{17}{13}-\frac{4}{13}\right)\times\frac{12}{17}\) = \((\frac{9}{14}+\frac{5}{14}):\frac{6}{7}\) = \(\frac{9}{12}\times\frac{9}{7}\times\frac{12}{19}\)
=\(\frac{4}{7}\times1\) = \(1\times\frac{12}{17}\) = \(1:\frac{6}{7}\) = \(\frac{9\times9\times12}{12\times7\times19}\)
=\(\frac{4}{7}\) = \(\frac{12}{17}\) =\(\frac{7}{6}\) = \(\frac{9\times9}{7\times19}=\frac{81}{133}\)
a,Cách 1: (6/11 + 5/11 ) x 3/7 Cách 2 :(6/11 + 5/11) x 3/7
= 1 x 3/7 =6/11 x 3/7 + 5/11 x 3/7
= 3/7 = 18/77 + 15/77
= 3/7
b, Cách 1:3/5 x 7/9 - 3/5 x 2/9 Cách 2 :3/5 x 7/9 - 3/5 x 2/9
= 7/15 - 2/15 = 3/5 x (7/9 - 2/9 )
= 1/3 = 3/5 x 5/9
= 1/3
c, Cách 1:(6/7 - 4/7) : 2/5 Cách 2: ( 6/7- 4/7 ) : 2/5
= 2/7 : 2/5 = 6/7 : 2/5 - 4/7 : 2/5
= 5/7 = 15/7 - 10/7
= 5/7
d,Cách 1:8/15 : 2/11 + 7/15 : 2/11 Cách 2:8/15 : 2/11 +7/15 : 2/11
= 88/30 + 77/30 =(8/15+7/15) :2/11
= 11/2 = 1 : 2/11
= 11/2
Bài 2 cậu tự làm nhé !
a) \(\frac{2}{9}+\frac{5}{6}\times\frac{4}{7}\)
\(=\frac{2}{9}+\frac{10}{21}\)
\(=\frac{44}{63}\)
b) \(\frac{21}{25}+\frac{4}{5}:\frac{8}{6}\)
\(=\frac{21}{25}+\frac{3}{5}\)
\(=\frac{36}{25}\)
c) \(\frac{17}{24}-\frac{1}{3}+\frac{3}{4}\)
\(=\frac{3}{8}+\frac{3}{4}\)
\(=\frac{9}{8}\)
a) \(\frac{2}{9}+\frac{5}{6}\times\frac{4}{7}=\frac{2}{9}+\frac{10}{21}=\frac{14}{63}+\frac{30}{63}=\frac{44}{63}\)
b) \(\frac{21}{25}+\frac{4}{5}\div\frac{8}{6}=\frac{21}{25}+\frac{4}{5}\times\frac{6}{8}=\frac{21}{25}+\frac{3}{5}=\frac{21}{25}+\frac{15}{25}=\frac{36}{25}\)
c) \(\frac{17}{24}-\frac{1}{3}+\frac{3}{4}=\frac{17}{24}-\frac{8}{24}+\frac{18}{24}=\frac{27}{24}=\frac{9}{8}\)
\(\frac{3}{5}\times\frac{6}{7}+\frac{3}{5}:7+\frac{6}{5}\)
\(=\frac{3}{5}\times\frac{6}{7}+\frac{3}{5}\times\frac{1}{7}+\frac{6}{5}\)
\(=\frac{3}{5}\times\left(\frac{6}{7}+\frac{1}{7}\right)+\frac{6}{5}\)
\(=\frac{3}{5}\times1+\frac{6}{5}\)
\(=\frac{3}{5}+\frac{6}{5}=\frac{9}{5}\)
~ Hok tốt ~
\(\frac{29}{12}:\frac{1}{2}-\frac{5}{12}:\frac{1}{2}-\frac{1}{2}\)
\(=\left(\frac{29}{12}-\frac{5}{12}\right):\frac{1}{2}-\frac{1}{2}\)
\(=2:\frac{1}{2}-\frac{1}{2}\)
\(=4-\frac{1}{2}=\frac{7}{2}\)
~ Hok tốt ~
a] 4/12 ; 5/12 ; 11/2 ; 1/4
b] 1 ; 9/12; 12/5 ; 11/3
c] 8/21; 6/11;8/7
d] 2/3 ;2/7 15/2
a]1/3 5/12 11/2 1/4
b]1 3/4 12/5 33/9
c]8/21 6/11 8/7
d]2/3 2/7 15/2
a) 1/14 b) 2/9 c) 11/4 d) 13/5
\(\frac{1}{2}-\frac{3}{7}=\frac{7}{14}-\frac{6}{14}=\frac{1}{14}\)
\(\frac{2}{3}-\frac{4}{9}=\frac{6}{9}-\frac{4}{9}=\frac{2}{9}\)
\(2+\frac{3}{4}=\frac{2}{1}+\frac{3}{4}=\frac{8}{4}+\frac{3}{4}=\frac{11}{4}\)
\(6-\frac{17}{5}=\frac{6}{1}-\frac{17}{5}=\frac{30}{5}-\frac{17}{5}=\frac{13}{5}\)